Efektivitas Strategi Marketing dan Operasional Terhadap Perkembangan Bisnis UMKM MyHazza - Sebastian, Derren; Kathleen, Felicia; Hartono, Ferdinand Emmanuel; Nathaniel, Jonathan; Wijaya, Renata Amanda; Gunawan, Stefanie; Budiman, Arief (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2024)
MSME businesses are one of the largest economic pillars in Indonesia, accounting for nearly 62% of the country's GDP. With such a significant contribution, competition among SME businesses is also intense. Many MSMEs are seeking to gain a competitive edge through technological channels such as Social Media, Microsoft Excel and others. This journal aims to explore the advantages of using these technologies in SME businesses from both a Marketing and Operations management perspective to advance MyHazza's business development. Specifically, it will focus on implementing Brand Awareness strategies on social media and adopting digital technology through digital recording systems for MyHazza's business operations. This implementation will take place from February to March 2024 offline during the Community Development event, and from April to June online to assist and guide the application of these aspects.